Cellular mechanisms of adaptive myelination: bridging the gap between animal studies and human cognition. Issue 2 (3rd April 2017) - Bujalka, Helena; Emery, Ben
ABSTRACT: Voelker and colleagues propose that we may illuminate learning-associated phenomena such as generalization by considering white matter plasticity. Consistent with this idea, human neuroimaging studies reveal learning-induced changes in adult white matter. Animal studies reveal that some forms of learning induce, and are dependent on, generation of new oligodendrocytes. Nevertheless, it remains unclear which alterations to myelin structure are most relevant to learning, and humans and rodents may profoundly differ in their capacity for oligodendrogenesis in adulthood. A full understanding of these issues will be critical to appreciating the role of adaptive myelination in human neuroplasticity.